2007
DOI: 10.1073/pnas.0607738104
|View full text |Cite|
|
Sign up to set email alerts
|

DgrA is a member of a new family of cyclic diguanosine monophosphate receptors and controls flagellar motor function in Caulobacter crescentus

Abstract: Bacteria are able to switch between two mutually exclusive lifestyles, motile single cells and sedentary multicellular communities that colonize surfaces. These behavioral changes contribute to an increased fitness in structured environments and are controlled by the ubiquitous bacterial second messenger cyclic diguanosine monophosphate (c-di-GMP). In response to changing environments, fluctuating levels of c-di-GMP inversely regulate cell motility and cell surface adhesins. Although the synthesis and breakdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
222
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(233 citation statements)
references
References 40 publications
9
222
0
2
Order By: Relevance
“…Thus, we found a novel mechanism of control of bacterial c-di-AMP synthesis via RadA-DisA interaction in M. smegmatis. In recent years, accumulating evidence has shown that cyclic dinucleotides widely function as second messengers that control multiple microbial phenotypes and physiological characteristics (4,5,(25)(26)(27)(28). Compared with the clearly characterized functions for c-di-GMP in many bacteria (4,5,28), much less is known about the control of c-di-AMP synthesis and its effects on bacterial growth.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we found a novel mechanism of control of bacterial c-di-AMP synthesis via RadA-DisA interaction in M. smegmatis. In recent years, accumulating evidence has shown that cyclic dinucleotides widely function as second messengers that control multiple microbial phenotypes and physiological characteristics (4,5,(25)(26)(27)(28). Compared with the clearly characterized functions for c-di-GMP in many bacteria (4,5,28), much less is known about the control of c-di-AMP synthesis and its effects on bacterial growth.…”
Section: Discussionmentioning
confidence: 99%
“…Although the product of fliL is essential for flagellar rotation, it is not considered a part of the hierarchy of the flagellum structure (Jenal et al, 1994). Instead, it has been suggested to have a role in controlling the switch between swimming and surface-associated lifestyles (Christen et al, 2007). Upregulation of fliL in the presence of methylamine thus may reflect a mechanism of activation of the flagellum machinery in response to the availability of a carbon source.…”
Section: Mobility and Adhesion Functionsmentioning
confidence: 99%
“…A motile cell can quickly reach a favorable niche in response to external stimuli and thus can successfully compete for a nutrient. However, synthesis and maintenance of the motility systems are energetically costly for the cell, and the motility functions are known to be tightly regulated by the availability of essential nutrients (Zhao et al, 2007;Christen et al, 2007). M. mobilis cells have been shown to be motile when grown in standard laboratory conditions (Kalyuzhnaya et al, 2006).…”
Section: Mobility and Adhesion Functionsmentioning
confidence: 99%
“…The first class, PilZ-domain proteins, has been linked to regulation of flagellar motility in Enterobacteria, Vibrio, and Caulobacter (10)(11)(12) and to the synthesis of alginate and type IV pili in Pseudomonas (13,14). The second class is less defined but shares an amino acid motif, RxxD, first identified as the allosteric site of product feedback inhibition in the diguanylate cyclase (DGC) PleD (15).…”
mentioning
confidence: 99%